Exploring the latest understanding on the role of immune mediators, genetic and environmental factors in pathogenesis of allergic rhinitis: a systematic review - Albloushi, Shaimaa; Al-Ahmad, Mona (Frontiers in Allergy, 2023)
Introduction Despite well-defined clinical phenotypes of chronic rhinitis, the underlying in-depth pathophysiological mechanism, particularly with reference to the involvement of immune mediators, genetic, and environmental factors, are still not fully understood. Therefore, our aim was to give updated information on the pathogenesis of allergic rhinitis (AR), with an emphasis on the role of cytokines in adults aged 18 years and above. Additionally, we investigated the impact of genetic and environmental factors in the pathogenesis of AR. Results A search in various databases identified 1,178 records, and 18 studies were ultimately selected from January 2018 to April 2023. The total sample size in our studies was 4,317, with 2,186 in the experimental and 2,131 in control groups, respectively. The mean age was 33.4 years, with 43% were male, while 57% were female. According to the selected studies, various factors, including immune mediators, particularly cytokines, genetic, and environmental factors, were identified in the development of AR. Conclusion The selected studies presented findings on different factors and sub-factors in the pathogenesis of AR, making it a challenge for us to compare their results. However, based on our findings, researchers can link our identified factors to potential therapies for AR.